The Sunrise Ultraviolet Spectropolarimeter and Imager: Standalone Polarimetric Calibration - Iglesias, Francisco Andres (2025)
Sunrise is a 1-m optical solar observatory carried aloft by a stratospheric balloon. It was developed to study magnetic fields and plasma flows in the solar atmosphere with very high spatial resolution and sensitivity. The Sunrise UV Spectropolarimeter and Imager (SUSI) operates in the 309--417 nm range, covering thousands of spectral lines that are poorly accessible from the ground and largely unexplored. The instrument includes a dual-beam polarimeter based on a rotating waveplate, a polarization beam splitter and two custom-made CMOS cameras. SUSI gathers data at high spectral, spatial and temporal resolution. These data are stored onboard during flight. Given that SUSI does not include a polarimetric calibration unit onboard, its polarimetric demodulation matrix is estimated during laboratory calibration measurements prior to its flight. The quality of this calibration is crucial to accurately demodulate the data post-flight and reach the instrument´s maximum polarimetric sensitivity goal of 1e-3 of the continuum intensity. In this paper, we report the results of eighth polarimetric calibrations of SUSI standalone, acquired at six different wavelengths using artificial LED light sources. The field-dependant demodulation matrices obtained are within the values expected from the design, including their polarimetric efficiencies and temporal stability. The matrices are also confirmed to satisfy the calibration repeatability criterion imposed by the SUSI sensitivity goal.